Avaliação de Desempenho do Processo de Manufatura do Café - Morais, L.; Massa, R.; Tavares, E.; Andrade, E. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance), 2015)
Globalization and advanced manufacturing technologies have forced manufacturing firms to increase productivity while reducing costs. At the same time, customers are increasingly demanding better products considering tangi- ble (e.g., smell, color, taste) and intangible (e.g., mark, fair treading, and envi- ronmental responsability) attributes. Currently, Brazil consolidates a position as the largest producer and exporter of coffee, accounting for 30% of the inter- national coffee market. This paper presents a stochastic model for performance evaluation and planning of coffee manufacturing process aiming at reducing the cost and time of the production cycle. An industrial case study shows the practical usability of the proposed models and techniques.